Effectiveness of application of methods of physical rehabilitation in patients of pasty age on osteoarthros of column diseases - Bakalyuk, T. G.; Stelmach, G. O. (Journal of Education, Health and Sport, 2017)
The article studies the clinical efficacy of the use of methods of physical rehabilitation in patients with osteoarthrosis of the knee joints. The rehabilitation program included post-isometric relaxation exercises and the volume pneumopressing technique for myocorrection, which contributed to the restoration of normal blood flow in the area of the nidus, strengthening muscles and improving joint function.